2013
DOI: 10.4103/0971-9784.119182
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic and hemodynamic management of a rare case of Brucella multivalvular endocarditis in cardiogenic shock undergoing emergency aortic valve replacement and mitral valve repair

Abstract: We describe a very rare case of human brucella multivalvular endocarditis. Patient presented in a state of cardiogenic shock with low urine output and a history of breathlessness. Patient was diagnosed to have brucellosis 2 months back by blood cultures and agglutination tests and was receiving doxycycline and rifampicin therapy. Echocardiography showed severe aortic regurgitation, moderate mitral regurgitation, severe left ventricular dysfunction and a mobile vegetation attached to the aortic valve. Patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Brucella endocarditis with cardiogenic shock is not well described in literature. Kandasamy et al reported one case of severe left ventricular dysfunction with severe aortic regurgitation and hemodynamic instability, in which patient survived after surgical and medical therapy [ 7 ]. Brucella endocarditis presenting with unusual case of septic shock after 50 years of quiescence was described by Haran et al in her case report [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brucella endocarditis with cardiogenic shock is not well described in literature. Kandasamy et al reported one case of severe left ventricular dysfunction with severe aortic regurgitation and hemodynamic instability, in which patient survived after surgical and medical therapy [ 7 ]. Brucella endocarditis presenting with unusual case of septic shock after 50 years of quiescence was described by Haran et al in her case report [ 8 ].…”
Section: Discussionmentioning
confidence: 99%